1986
DOI: 10.1139/t86-073
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of geogrid and geotextile reinforced earth slabs

Abstract: Presented herein is a comparison of the results of laboratory model tests used to study the bearing capacity of geogrid and geotextile reinforced earth slabs. The parameters studied were the coefficient of friction between the geotextile and the soil, pull-out resistance between the geogrid and the soil, depth below the footing of the first layer of reinforcement, vertical spacing of the layers, number of layers, width size of a square sheet of reinforcement, and tensile strength of the reinforcement. For both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(89 citation statements)
references
References 3 publications
6
65
2
2
Order By: Relevance
“…These results confirm the findings by Sing [11] , which were based on the study of square footings on sand reinforced with mild steel grids (optimum depth ratio was about 0.25). However, the results are in contrast with reports of other researches [7,12,13] , which, most likely is due to difference in material properties and the geometric dimensions of the foundation and reinforcement. Hence, it may be concluded that; reporting a single value of u/B for optimum bearing capacity of geogrid reinforced soil is flawed as reported by other researchers such as; Adams and Colin [2] , Yetimuglu et al [4] , and Guido et al [8] .…”
Section: Placement Of Reinforcementcontrasting
confidence: 99%
See 2 more Smart Citations
“…These results confirm the findings by Sing [11] , which were based on the study of square footings on sand reinforced with mild steel grids (optimum depth ratio was about 0.25). However, the results are in contrast with reports of other researches [7,12,13] , which, most likely is due to difference in material properties and the geometric dimensions of the foundation and reinforcement. Hence, it may be concluded that; reporting a single value of u/B for optimum bearing capacity of geogrid reinforced soil is flawed as reported by other researchers such as; Adams and Colin [2] , Yetimuglu et al [4] , and Guido et al [8] .…”
Section: Placement Of Reinforcementcontrasting
confidence: 99%
“…This value is slightly higher than 0.15-0.25 suggested by others [4,11] . Furthermore, Guido et al [7] , and Akinmusuru and Akinbolade [12] reported that, as the vertical spacing increases, the BCR value decreases accordingly. Guido et al [13] , indicated that, although the BCR value decreased with increasing vertical spacing, the trend of BCR variation with vertical spacing was different for different geogrids.…”
Section: Spacing Of Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only limited information in the literature about the effect of different reinforcement types. Guido et al [22] and Chen [23] have investigated the reinforcement types and the general outcome was that geogrids show superior performance compared to geotextiles. Mandal and Manjunath [24] investigated the bearing capacity behavior of Geogrid and bamboo stick reinforcements for strip plates on dense sand.…”
Section: Introductionmentioning
confidence: 99%
“…Since the original work by Binquet and Lee, several laboratory model test studies have been published relating to the improvement of the load-bearing capacity of shallow foundations supported by sand reinforced with various materials such as geogrids [3,4], geotextiles [5], rope fibers [6], metal strips and metal bars [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%